A Newly Synthesized Tris(crown ether) Ionophore for Assisted Ion Transfer at NanoITIES Electrodes. Issue 4 (12th February 2020) - Chen, Ran; Yang, Anna; Chang, Albert; Oweimrin, Philip F.; Romero, Julian; Vichitcharoenpaisarn, Pitchaya; Tapia, Stephanie; Ha, Kevin; Villaflor, Christopher; Shen, Mei
Abstract: Assisted ion transfer at a pipet‐supported interface between two immiscible electrolyte solutions (ITIES) have become a prominent method for the detection of various ionic species and for studying ionic complexation. A typical ionophore contains one binding center to ions such as dibenzo‐18‐crown‐6 (DB18C6). It is unknown how the detection of ions changes when assisted by an ionophore with multiple crown ether moieties. Here, we synthesized a new tris(crown ether) ionophore, TriBCE, which is composed of three 18‐crown‐6 moieties connected to a common o‐phenylene ethynylene cyclic trimer center, and employed TriBCE for the assisted ion transfer of various environmentally relevant heavy‐metal ions (i. e. Mg 2+, Cu 2+, Cd 2+ and Li + ) and a neurotransmitter (dopamine) at nanoITIES pipet electrodes. The half‐wave transfer potentials for those ions were less positive by 123±28 mV when assisted by tris (crown ether), TriBCE, compared to mono(crown ether), DB18C6. The binding constants, Gibbs free energy, and the stoichiometric coefficients of ionic complexation with TriBCE were measured and compared to that of DB18C6 to reveal that ionophore with multiple binding moieties enables easier transfer of these ions. Abstract : Detecting ions : Tris (crown ether) ionophore enables easier ion transfer compared to mono (crown ether) ionophore. Environmentally relevant metal ions (Mg 2+, Cu 2+, Cd 2+, and Li + ) and a neurotransmitter (dopamine) are successfully detected at the nanoscale interface between two immiscible electrolyte solutions (nanoITIES), assisted by the newly synthesized tris(crown ether) ionophore.